Pojęcie hipotek dawnych po nowelizacji ustawy o księgach wieczystych i hipotece — kwestie intertemporalne - Stangret-Smoczyńska, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
Amendments to the Land Register and Mortgage Act that came into force on 20 February 2011 provide a new mortgage structure. As regards old mortgage, the rule is that old regulations are applied to ordinary mortgage and to bail mortgage. However, as regards independent bail mortgage established before the amendments to the Act came into force the new regulations are applied with the exception of regulations regarding disposal of a vacated mortgage rank. Therefore, it is justified to use the concept of old mortgage to ordinary mortgage and to bail mortgage established together with ordinary mortgage only. In the author’s opinion after transferring ordinary mortgage into bail mortgage the old regulations would be applied to the bail mortgage.
Keywords: hipoteka; hipoteka zwykła; hipoteka kaucyjna; nowelizacja; ustawa o księdze wieczystej i hipotece